2022
DOI: 10.3389/fchem.2022.1078877
|View full text |Cite
|
Sign up to set email alerts
|

Efficient removal of tetracycline from aqueous solution by K2CO3 activated penicillin fermentation residue biochar

Abstract: In this study, biochar was prepared using penicillin fermentation residue (PR) as the raw material by different methods. The adsorption behavior and adsorption mechanism of biochar on tetracycline (TC) in an aqueous environment were investigated. The results showed that K2CO3 as an activator could effectively make porous structures, and that biochar with mesoporous or microporous could be prepared in a controlled manner with two kinds of different activation methods, the dry mixing method and the impregnation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…35,36 The microporous and mesoporous structures on the surface of biochar aren't key factors for the adsorption of TC. Zhu et al 37 found that the presence of micropores has little effect on the adsorption of tetracycline, while Liu et al 38 demonstrated that the adsorption of tetracycline on mesoporous biochar is negatively impacted. In order to further clarify the inuence of reaction conditions on the degree of graphitization and to further investigate how the fabrication condition affects the crystallographic structures of BC, we used XRD and Raman to investigate the structural change of BC (Fig.…”
Section: And S1 †)mentioning
confidence: 99%
“…35,36 The microporous and mesoporous structures on the surface of biochar aren't key factors for the adsorption of TC. Zhu et al 37 found that the presence of micropores has little effect on the adsorption of tetracycline, while Liu et al 38 demonstrated that the adsorption of tetracycline on mesoporous biochar is negatively impacted. In order to further clarify the inuence of reaction conditions on the degree of graphitization and to further investigate how the fabrication condition affects the crystallographic structures of BC, we used XRD and Raman to investigate the structural change of BC (Fig.…”
Section: And S1 †)mentioning
confidence: 99%